Mitotane-driven apoptosis in adrenocortical carcinoma: A molecular insight (Annals of Medical Research, 2024)
Aim: The aim of this study was to investigate the responses of antiapoptotic Bcl-2 and proapoptotic Bid genes to Mitotane and other chemotherapy drugs in Adrenocortical Carcinoma (ACC) cells. The purpose was to understand the effects of these chemotherapy drugs on apoptosis-related genes in ACC and to identify potential treatment pathways.Materials and Methods: The study involved the use of ACC cells to assess gene expressions in response to treatment with Mitotane, Etoposide, and Cisplatin. Gene expression levels of Bcl-2 and Bid were measured after drug exposure, providing insight into the modulation of apoptosis pathways by Rt-qPCR.Results: The results demonstrated that Mitotane notably affected the expression of the proapoptotic Bid gene in ACC cells, promoting apoptosis. Cisplatin increased the expression of the antiapoptotic Bcl-2 gene and decreased the expression of the proapoptotic Bid gene compared to Mitotane.Conclusion: This study showed that Mitotane, like other chemotherapy drugs, affects the expression of key apoptosis-related genes in ACC cells. Mitotane significantly affected the proapoptotic Bid gene, indicating its potential as a treatment option for ACC. These findings suggest that Mitotane affects ACC cells, highlighting its importance in ACC therapy.
Keywords: ACC; Apoptosis; Bid gene; Bcl-2 gene; Mitotane